Designing Vendor Performance Criteria Using Analytic Hierarchy Process Method On The Engineering Procurement Construction Project Company - Annisa Nursyahbani; Atya Nur Aisha; Intan Permatasari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Indonesia's electrical power supply is insufficient to meet the population's demands. Therefore, the rise of Renewable Energy (RE) is anticipated to fulfill the needs. One of Indonesia's renewable energy industries implementing project management in its operations encountered delays in its engineering procurement construction project due to material delay, and the project's quality failed to meet requirements due to an incompetent vendor. Furthermore, the existing key performance indicators were insufficiently comprehensive, lacked criteria related to business permits, and had unclear Critical Success Factors (CSF). The primary goal was to develop narrowly focused criteria to evaluate vendor construction performance through Multi-Criteria Decision-Making (MCDM). The Analytical Hierarchy Process (AHP) method is one of the techniques utilized in MCDM to determine the ranking of alternatives based on selection criteria that have hierarchical interdependence relationships. This study produced six main criteria based on literature studies, including management capability, financial capability, quality, delivery time, customer services, and safety. The most important sub-criteria from the results of this study are speed and accuracy of delivery time with a weight of 23,90%, where the factor of completing the project activity on time is a key factor for project success. For further handling, this criterion is considered as CSF for vendor selection at EPC projects, especially in the RE industry. Keywords: Analytic Hierarchy Process (AHP), Key Performance Indicator (KPI), Project Management, Procurement Management, Vendor